Grouper cage culture device - YANG QINGSHAN; LIN GUOFU; YANG LIHUA; LIN GUOCONG; YANG WENGUANG (2015)
The invention discloses a grouper cage culture device which comprises a rectangular frame. The bottom of the frame is provided with a culture net, multiple floating barrels are arranged all around the frame, floating foam is arranged in the middle of the frame, a support frame is arranged on the floating foam, a foodstuff storage tank is arranged on the support frame and connected with a feeding tube, the feeding tube extends out of the floating foam, a magnetic valve is arranged on the feeding tube and connected with a control module, and the control module is connected with a timer. The grouper cage culture device has the advantages that the stability and the reliability are achieved, feeding of grouper can be conducted periodically, the labor cost is reduced, and the time and the labor are saved.